(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: - The carrying angle is the angle placed between the median axis of arm and median axis of forearm in full extension and supination position. This angle provides the forearms a clear movement with respect to the hips while walking and is important when carrying objects. Carrying angle is examined in various pre-placement medical examination. Carrying angle can be used to differentiate between male and female upper limb. This can be used in partial identification if rich regional data is systemically and statistically collected. Objective:-To collect the statistical data values of carrying angle in both the sexes of Ajmer region. Observing any difference between the caring angle of dominant and non-dominant hand of same individual Method: - A cross-sectional study was carried out with right handed 100 males and right handed 100 females and variations in carrying angle between males and females were calculated using Goniometer. The value is analyzed by mean, standard deviation Results: - In males, mean carrying angle of both upper limbs is 10.720 where as in females mean carrying angle of both upper limbs is found 13.420. Conclusion: The present study showed that the carrying angle was greater in females than in males and it was greater in non-dominant arm than in dominant arm.